Recognition of emotions and affective attitudes in children with attention-deficit hyperactivity disorder - Plećević, Vladan; Djoković, Sanja; Kovačević, Tamara (Vojnosanitetski pregled, 2021)
Background/Aim. Children with attention-deficit hyperactivity disorder (ADHD) show lower degree of recognition of their own emotions and greater behavioral difficulties than children who do not have this disorder. This also affects the recognition of other people’s emotions that are expressed not only by their language content, but also by their facial expression and the way they express the emotional message through speech. Most research in this area focuses on recognizing emotions based on facial expressions rather than on emotions in speech. The aim of this study was to examine how children with ADHD recognize emotions in speech (joy, anger, fear, sadness) and affective attitudes (threat and commandment) in relation to children of typical development. Methods. The study included 31 children with ADHD and 29 typical developmental children aged 6 to 13. To assess the ability to recognize emotions and affective attitudes, a corpus of Speech Emotional Expression and Attitudes (Govorna emocionalna ekspresija i stavovi – GEES, in Serbian) was used. This corpus included sentences that expressed emotions of anger, joy, fear, and sadness, and of affective attitudes, threat and command. Results. The results obtained showed that children with ADHD had worse recognition of emotions and affective attitudes in speech than children of typical development (t = 8.81; p = 0.000). Joy was the only emotion where no statistically significant difference was found. In all other emotions and affective attitudes, statistically significant differences were found (p < 0.01). Also, the results showed that there was a statistically significant association between age and recognition of emotion and affective attitudes in both groups, but this association was more pronounced in children of typical development. Conclusion. The results of this study provided important clues about the perception of emotions and affective attitudes in speech in children with ADHD. These results are very important for the conception of therapeutic procedures, especially in the development of strategies for modeling the behavior of children with ADHD.